Brick soil cement with addition of tire rubber waste (Research, Society and Development, 2021)
This work has as objective to investigate the physical and mechanical properties of the soil-cement brick with the use of tire rubber residues. It is an alternative to solve a serious environmental problem that exists nationwide, as more than 30 million tires are discarded, as the vast majority are disposed of in inappropriate places, helping to spread diseases and pollute the environment. The methodology used consisted of laboratory tests of the limit of liquidity, plasticity of the soil and after molding, the bricks were submitted to the compressive and absorption resistance test. The soil presented high hygroscopic moisture above the value established by the standard and all percentages with tire residue did not obtain compressive strength above 2 Mpa and the individual absorption values obtained were higher than those indicated by the standard for soil-cement brick. It is concluded that the bricks were not approved in terms of simple compression tests, water absorption, liquidity limits, plasticity limit, as they do not meet the requirements established in NBR 8491/2012 and NBR 10833/2012.